2016
DOI: 10.14687/jhs.v13i3.4277
|View full text |Cite
|
Sign up to set email alerts
|

School counselors’ thoughts about psychosocial problems and guidance needs of students with learning disabilities<p>Okul rehber öğretmenlerinin özgül öğrenme güçlüğü olan öğrencilerin psikososyal sorunları ve rehberlik ihtiyaçları hakkındaki görüşleri

Abstract: Learning disability is a developmental disorder that manifests itself in the acquisition of academic skills including reading, writing, and mathematics. School counselors play a crucial role in identification and diagnose of students with learning disability. Moreover, school counselor office take necessary steps for prevention and intervention of learning difficulties in school settings.  The goal of the study was to scrutinize school counselors’ thoughts and perceptions about these students’ guidance needs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 9 publications
2
5
0
Order By: Relevance
“…For this reason, it is seen that teachers think that they do not have the necessary knowledge and skills regarding the process of recognizing and guiding a student at risk of SLD (Balcı, 2019;Çoğaltay & Çetin, 2020) and educational methods to meet their needs (Balcı, 2019;Birol & Aksoy-Zor, 2018). Similarly, there are studies in which researchers have concluded that teachers' education levels for SLD are insufficient (Birol & Aksoy-Zor, 2018;Çoğaltay & Çetin, 2020;Fırat & Koçak, 2018;Gül et al, 2016;Urfalı-Dadandı et al, 2016). When these findings are brought together, it can be said that the most important factor in applying the earliness principle in the diagnosis process is the knowledge level of the teachers.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…For this reason, it is seen that teachers think that they do not have the necessary knowledge and skills regarding the process of recognizing and guiding a student at risk of SLD (Balcı, 2019;Çoğaltay & Çetin, 2020) and educational methods to meet their needs (Balcı, 2019;Birol & Aksoy-Zor, 2018). Similarly, there are studies in which researchers have concluded that teachers' education levels for SLD are insufficient (Birol & Aksoy-Zor, 2018;Çoğaltay & Çetin, 2020;Fırat & Koçak, 2018;Gül et al, 2016;Urfalı-Dadandı et al, 2016). When these findings are brought together, it can be said that the most important factor in applying the earliness principle in the diagnosis process is the knowledge level of the teachers.…”
Section: Discussionmentioning
confidence: 98%
“…When the body of literature in Turkey has seen that the study group of searches are generally composed of educators. In the literature on SLD, it is seen that there are studies on educator's knowledge (Çoğaltay & Çetin, 2020;Fırat & Koçak, 2018;Gever, 2017;Gül et al, 2016), educator's problems and demands (Balcı, 2019;Birol & Aksoy-Zor, 2018;Göksoy & Öksüz, 2019;Kılıç, 2020;Sadan, 2018;Sivrikaya & Yıkmış, 2016;Urfalı-Dadandı et al, 2016) and the program to address the requirements of the educators (Başar & Göncü, 2018;Deniz, 2019) and the children with SLD (Aydın, 2017;Çıkılı et al, 2019;Görgü, 2017;Görgün & Melekoğlu, 2019). When the evaluation process is considered, it is seen that the studies mostly focus on teachers' opinions about the educational evaluation process of children with special needs.…”
Section: Yazarların Katkı Düzeylerimentioning
confidence: 99%
“…Our analysis showed that studies with teachers were mostly done to determine teachers' knowledge level about dyslexia. Findings of this review showed that the majority of teachers (a) do not have sufficient knowledge about dyslexia (Balcı, 2019), (b) feel inadequately prepared to work with these students (Balcı, 2019;Dadandı et al, 2016), (c) do not have the professional skills necessary to diagnose dyslexic students (Balcı, 2019;Doğan, 2013), (d) do not know the instructional methods to support dyslexic students (Balcı, 2019), (e) do not have sufficient training on dyslexia (Balcı, 2019), and (f) have misinformation about dyslexia (Gül et al, 2016).…”
Section: Teacher Researchmentioning
confidence: 95%
“…School counselors have an influential role in diagnosing and psychosocial support for students with SLD. In this context, Dadandı et al (2016) examined the awareness levels of school counselors working with students with SLD in secondary schools regarding these students' psychosocial problems and guidance needs. A total of 12 school counselors participated in the study.…”
Section: Research With Teachers In the Context Of Dyslexiamentioning
confidence: 99%
“…These studies found that the school counsellors' lack of sufficient knowledge about students with LD poses another problem. Dadandı et al (2016) determined that school counsellors feel inadequate when working with students with LD. The course on LD given to school counsellor candidates as part of the Guidance and Psychological Counselling departments in Turkey are no longer compulsory following the revisions in the undergraduate programs in 2018.…”
Section: The Context In Turkeymentioning
confidence: 99%